2007
DOI: 10.1002/prca.200700522
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes secrete exosomes containing major myelin and stress‐protective proteins: Trophic support for axons?

Abstract: Oligodendrocytes synthesize the CNS myelin sheath by enwrapping axonal segments with elongations of their plasma membrane. Spatial and temporal control of membrane traffic is a prerequisite for proper myelin formation. The major myelin proteolipid protein (PLP) accumulates in late endosomal storage compartments and multivesicular bodies (MVBs). Fusion of MVBs with the plasma membrane results in the release of the intralumenal vesicles, termed exosomes, into the extracellular space. Here, we show that cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
426
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 464 publications
(433 citation statements)
references
References 79 publications
5
426
1
1
Order By: Relevance
“…These results may imply a novel immunosuppressive action of the drug, that is, FTY720 treatment causes inhibition of S1P signalling on MVEs, which blocks exosomal MVE maturation, that may affect early steps of immunization, for example, an exosome-related phenomenon such as antigen presentation by dendritic cells. Indeed, oligodendrocytes secrete relatively large amounts of exosomes enriched in myelin proteolipid protein in the central nervous system, a candidate of autoantigen in multiple sclerosis 30,61 . As for the mechanism of depletion of S1P 1 receptors from MVEs, it has recently been shown that S1P 1 receptors were accumulated to Golgi/trans-Golgi network and scarcely found in endosomes for several hours after treatment of cells with FTY720 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…These results may imply a novel immunosuppressive action of the drug, that is, FTY720 treatment causes inhibition of S1P signalling on MVEs, which blocks exosomal MVE maturation, that may affect early steps of immunization, for example, an exosome-related phenomenon such as antigen presentation by dendritic cells. Indeed, oligodendrocytes secrete relatively large amounts of exosomes enriched in myelin proteolipid protein in the central nervous system, a candidate of autoantigen in multiple sclerosis 30,61 . As for the mechanism of depletion of S1P 1 receptors from MVEs, it has recently been shown that S1P 1 receptors were accumulated to Golgi/trans-Golgi network and scarcely found in endosomes for several hours after treatment of cells with FTY720 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other cells in the CNS such as astrocytes [68,69], microglial cells [70] and oligodendrocytes [71] release EMVs (table 3). Astrocytes can release EMVs by an ATPinduced stimulation of P2X7 receptors followed by an action of acid sphingomyelinase [72].…”
Section: (C) Central Nervous Systemmentioning
confidence: 99%
“…The oligodendrocyte exosomes contain myelin proteins such as PLP and CNP, glycolytic enzymes, stress protective proteins, mRNA and miRNA [71] (table 3). Axonally released glutamate activates exosome release from oligodendroglia mediated mainly by glial NMDA receptors [77].…”
Section: (C) Central Nervous Systemmentioning
confidence: 99%
“…Confocal microscopy studies suggested co-localization of PDGFR␣ with sulfatides in ASA ϩ/ϩ and to a lesser extent in ASA Ϫ/Ϫ NPs (data not shown). There is evidence that sulfatides are components of exosomal membranes (82). However, exosomes isolated from NPs appeared to contain little if any sulfatide (data not shown).…”
Section: Discussionmentioning
confidence: 97%